Digital Habitus in the Transformation of Food Processed Product MSMEs in Rural Areas: A Case Study of Kediri Young Entrepreneur (KYE) Association - Moh. Hamzah Fansuri; Damayanti, Salsabila; Habibi, Ahmad Wildan (Department of Social Development and Welfare, Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2025)
This study explores the digital transformation practices of rural micro, small, and medium enterprises (MSMEs) food processing products associated with the Kediri Young Entrepreneur (KYE) Association. This study investigates how MSME practitioners integrate digital technologies at both the micro and macro levels. For example, they use instant messaging apps to coordinate and make group decisions, social media sites to create content, build brands, and gain market visibility through algorithms, e-marketplaces to make transactions easier and grow the market, and digital payment systems to connect operations. Drawing on Pierre Bourdieu’s practice theory, this qualitative interpretive study analyzes how digitalization intersects with structure and agency and how social networks emerge among actors in rural MSME food-processing product production. This study reveals several important finding: (1) digital habitus is formed through an integrated, evolving structure in which repeated digital practices become internalized dispositions; (2) there is a symbolic struggle in the form of a struggle for power over digital technology capabilities among MSME food processing products actors; (3) strategic mobilization in the form of economic, social, cultural and symbolic capital to gain legitimacy, strengthen capital and competitive advantage. This study concludes that digital transformation, showed up in regular digital coordination, platform-based marketing, marketplace integration, and digital money management, is not merely a technical shift but also a social transformation reflecting the cultural tendencies, power structures, and strategic actions actors in MSME food processing product markets, where the KYE Association serves as an arena that bridges collective traditions with digital innovation